2016
DOI: 10.2139/ssrn.2844729
|View full text |Cite
|
Sign up to set email alerts
|

Is Corruption Efficiency-Enhancing? A Case Study of Nine Central and Eastern European Countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
2
14
0
1
Order By: Relevance
“…Early evidence about the negative impact of corruption on economic growth based on a cross-country empirical analysis is presented in Mauro (1995). Similar results are obtained by Wei (1999), Méon and Sekkat (2005), Gamberoni et al (2016). For excellent reviews of the literature, see Svensson (2005), , Ugur and Dasgupta (2011), and IMF (2016).…”
supporting
confidence: 73%
“…Early evidence about the negative impact of corruption on economic growth based on a cross-country empirical analysis is presented in Mauro (1995). Similar results are obtained by Wei (1999), Méon and Sekkat (2005), Gamberoni et al (2016). For excellent reviews of the literature, see Svensson (2005), , Ugur and Dasgupta (2011), and IMF (2016).…”
supporting
confidence: 73%
“…4 Early evidence about the negative impact of corruption on economic growth based on a cross-country empirical analysis is presented in Mauro (1995). Similar results are obtained by Wei (1999), Méon and Sekkat (2005), Gamberoni et al (2016). For excellent reviews of the literature, see Svensson (2005), Campos et al (2010), Ugur andDasgupta (2011), andIMF (2016).…”
supporting
confidence: 71%
“…In Annex D we show the (again quite low) correlations between changes in labour and capital misallocation by sector, as well as reporting input misallocation dynamics across 2-digit industries within the heterogeneous manufacturing sector. Gamberoni et al (2016) have found that for a sample of Central and Eastern European countries there is evidence of convergence in both capital and labour misallocation or of their inverse, allocative efficiency. We too find descriptive evidence of a negative correlation between the initial level of dispersion in 2002 and subsequent growth rates at the country-sector level ( Figure 5), in particular for capital misallocation.…”
Section: Developments In Input Misallocationmentioning
confidence: 99%
“…The difference in the variation of the two types of input misallocation, highlighted in Section 3, could possibly suggest that capital-specific factors rather than common shocks were mainly at work in the period under study. Similarly to Gamberoni et al (2016), we adopt a conditional convergence model, based on Barro and Sala-i-Martin (2004), which takes the following form:…”
Section: The Determinants Of Input Misallocation: Panel Regression Anmentioning
confidence: 99%